Cascade Conversion of Cellobiose to Gluconic Acid: The Large Impact of the Small Modification of Electronic Interaction on the Performance of Au/TiO2 Bifunctional Catalysts. Issue 9 (14th September 2018) - Morawa Eblagon, Katarzyna; Pastrana‐Martínez, Luisa M.; Pereira, Manuel F. R.; Figueiredo, José L.
Abstract: The effect of the type and properties of TiO2 and the addition of graphene oxide (GO) was studied in Au/TiO2 bifunctional catalysts, applied for cascade conversion of cellobiose to gluconic acid. Au was supported on three TiO2 materials with varied phase composition (100 % anatase or 80 % anatase/20 % rutile), particle size and surface chemistry. An exceptional yield of gluconic acid reaching 85 % was attained in a very short time of only 2 hours over Au supported on in‐house made TiO2 . It was shown that the best performing catalyst had an "electron rich" Au metal phase and oxygen vacancies situated in close proximity to the metal‐support interface. Further, the electronic state in these catalysts was modified by addition of GO to the TiO2 supports, which was followed by high temperature reduction to form TiO2 _rGO (TiO2 ‐reduced GO) composites. It was found that the presence of only small amount of rGO hindered the charge transfer from TiO2 to Au, leading to a metallic gold as shown by XPS. In addition, the presence of rGO impeded the formation of oxygen defects in TiO2 supports. This in turn had a negative impact on the rate and selectivity of glucose oxidation, the second step of the tandem process. To sum up, the unique interaction between "electron rich" Au nanoparticles and the neighboring oxygen vacancies on anatase TiO2 was found to play essential role in obtaining outstanding catalytic performance in the tandem oxidation of cellobiose to gluconic acid. Abstract : Electron heist : Bifunctional Au supported on various TiO2 materials was applied in cascade oxidation of cellobiose to gluconic acid. An exceptional yield of gluconic acid, reaching 85 % was obtained using "electron rich" Au/TiO2 containing oxygen vacancies in the anatase support. The metal ‐support interaction in this catalytic system can be influenced by a very small addition of graphene oxide (GO) to the TiO2 which "snatches" the electrons.